A novel experimental method to the internal thrust of rocket-based combined-cycle engine. (September 2021) - Gu, Rui; Sun, Mingbo; Li, Peibo; Cai, Zun; Yao, Yizhi
Highlights: The method can be used to study high altitude performance of the RBCC engine. There is a great moment to the engine when the rocket turns on. The air mass flow rate is the most important factor to the RBCC engine. Abstract: The rocket-based combined-cycle engine is considered as a promising scheme to achieve affordable and reusable space transportation. Under the ejector mode, the air mass flow rate is limited by aerodynamic chocking in the mixer of the engine. In other words, the air mass flow rate is determined by the downstream mixing. However for the requirement of critical air mass flow rate, the air stream supplying and the internal thrust measurement are difficult to conduct in the conventional ground experimental facilities. And more importantly, the critical thrust performance is also hard to obtain. A novel experimental facility is introduced in which the air stream is entrained from the ambient atmosphere. The inlet throat is large enough to make sure the inflow air is throttled by aerodynamic chocking in the mixer. In addition, a supersonic ejector is used to simulate the pressure environment at a high altitude. The internal thrust under different flight conditions can be calculated through the measured parameters in the experiments. The results show that the novel experimental facility can be used to study the thrust performance of rocket-based combined-cycle engine in ejector mode. The test precision is acceptable and the thrust difference between the test and the simulation is less than 8%. With the increase of the inflow Mach number, the engine internal drag under the cold flow condition rises as well as the specific impulse augmentation. The specific impulse augmentation could be 16.5% when the entrainment ratio is 1.88 at a simulated condition of H6.8 km / Mach 1.2.